MANAJEMEN PELAYANAN PENANGGULANGAN BENCANA DI KOTA BOGOR - Susanti, Rani; Iskandar, Abubakar; Heryati, Ade (Universitas Djuanda, 2020)
Disasters occur because of two conditions, namely the existence of events or disorders that thraeten and destroys (hazard) and vulnerablility of the community. If there is damage, but the community is not vulnerable, it means that the community handles its own disturbing event or the risk becomes low, while if the condition of the community is vulnerable, but no threating events will occur, there will be no disaster. The purpose of this study is to analyze the Implementation of Natural Disaster Management policies, explain Management of Natural Disaster Manajement, Analyze the Utilization of Natural Disaster Management Resources for services provided by BPBD Bogor City. This research uses quantitative and qualitative approaches, the collection technique is observation, interview and documentation, a sample of 50 respondents, while the data analysis uses the flow model and correlation and Likert scale. The results showed the relationship between buliding material assistence with an earthquake of 0,921, meaning that if there was building material assistance, it could overcome losses caused by the earthquake. Keywords : Disasters, Management, Assistence